DAMPs and radiation injury - Yamaga, Satoshi; Aziz, Monowar; Murao, Atsushi; Brenner, Max; Wang, Ping (Frontiers in Immunology, 2024)
The heightened risk of ionizing radiation exposure, stemming from radiation accidents and potential acts of terrorism, has spurred growing interests in devising effective countermeasures against radiation injury. High-dose ionizing radiation exposure triggers acute radiation syndrome (ARS), manifesting as hematopoietic, gastrointestinal, and neurovascular ARS. Hematopoietic ARS typically presents with neutropenia and thrombocytopenia, while gastrointestinal ARS results in intestinal mucosal injury, often culminating in lethal sepsis and gastrointestinal bleeding. This deleterious impact can be attributed to radiation-induced DNA damage and oxidative stress, leading to various forms of cell death, such as apoptosis, necrosis and ferroptosis. Damage-associated molecular patterns (DAMPs) are intrinsic molecules released by cells undergoing injury or in the process of dying, either through passive or active pathways. These molecules then interact with pattern recognition receptors, triggering inflammatory responses. Such a cascade of events ultimately results in further tissue and organ damage, contributing to the elevated mortality rate. Notably, infection and sepsis often develop in ARS cases, further increasing the release of DAMPs. Given that lethal sepsis stands as a major contributor to the mortality in ARS, DAMPs hold the potential to function as mediators, exacerbating radiation-induced organ injury and consequently worsening overall survival. This review describes the intricate mechanisms underlying radiation-induced release of DAMPs. Furthermore, it discusses the detrimental effects of DAMPs on the immune system and explores potential DAMP-targeting therapeutic strategies to alleviate radiation-induced injury.